Econometric analyses with backdated data: unified Germany and the euro area - Elena Angelini; Massimiliano Marcellino (European Central Bank (ECB), 2007)
In this paper we compare alternative approaches for the construction of time series of macroeconomic variables for Unified Germany prior to 1991, and then use them for the construction of corresponding time series for the euro area. The resulting series for Germany and the euro area are compared with existing ones on the basis of both descriptive statistics and results of econometric analyses conducted with the alternative time series. We find that more sophisticated time series methods for backdating can yield sizeable gains.
Keywords: C32; C43; C82; 330; Backdating; euro area; factor model; Unified Germany; Zeitreihenanalyse; Nationaleinkommen; Deutschland; EU-Staaten